Modeling and Optimization of Cefixime Removal from Aqueous Solutions by Potato Starch Using Response Surface Methodology (RSM) - Fatemeh Sadat Tabatabaei; Mahdi Asadi-Ghalhari; Reznaneh Esmaeili (Mazandaran University of Medical Sciences, 2020)
Introduction and purpose: Cefixime (CFX) is one of the most extensively used antibiotics across the world. Nonetheless, the entrance of this pharmaceutical compound into water resources has posed a serious problem to the environment. With this background in mind, the present study aimed to analyze the effectiveness of CFX removal from aqueous solutions by potato starch. Methods: The current study assessed the effect of four main effective parameters, namely pH (3-9), potato starch dose (0-300mg/L), CFX initial concentration (0-16mg/L), and retention time (20-120min), on CFX removal using Response Surface Methodology (RSM). Results: Under the optimum conditions, the maximum CFX removal efficiency was reported as 65.57%, with the optimum values of pH=4.5, potato starch dose=225mg/L, CFX initial concentration=7.9, and retention time=95min. As demonstrated by the results of RSM, the current study follows the quadratic model (R2=0.987). Conclusion: Considering the appropriate results of CFX removal by potato starch, it is recommended to be used as a successful method to remove this contaminant from water sources.